Destructive Test Material SA516 70N Untuk Kualifikasi Pengelasan Standar ASME BPVC Sec. IX-2021 - Benny Haddli Irawan; Nugroho Pratomo Ariyanto; Jonas Felix Siregar (Jurnal Teknik Mesin, 2023)
This research contains about destructive test for WPS qualification (welding qualification record) in making pressure vessel. WPS can be declared qualified if they have PQR (procedure qualification record). In making PQR required testing destructive test the test is carried out by damaging the specimen based on ASME standards (american society of mechanical engineers) BPVC (boiler pressure vessel code) Sec. IX-2021 with SA516 70N material. Indestructive test for this welding qualification, there are 4 types of testing with the number of specimens to be tested, namely: testing tensile (2 specimens), testing bend (4 specimens), testing charpy iMPact (2 sets or 6 pcs specimen), and testing hardness vickers (1 specimen). Number of specimens tensile and bend specified in ASME BPVC Sec. IX-2021 on QW-451.1 and for the number of test specimens charpy iMPact has been specified in ASME BPVC Sec. VIII. 1-2021 on UG-84 as well as for total specimen hardness vickers specified in NACE MR0175/ISO 15156-2:2023E table A.1. Results of testing tensile obtained a figure of 542 MPa (N/mm2) with a minimum requirement of 485 MPa (N/mm2), testing bend no open discontinuities found, for test results charpy iMPact the smallest is 47 joules with a minimum requirement of 20 joules for single hairy. And for testing hardness vickers highest value 217 HV on section weld cap with requirements weld root is 250 HV while the highest value is on the part weld cap is 275 HV. The results of this test indicate that the welding procedure complies with the requirements and conditions set out in ASME BPVC Sec. IX-2021 in testing destructive test.